2008
DOI: 10.1103/physrevlett.100.207001
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Josephson Effect with Magnetic Feedback in a Superconductor-Ferromagnet Heterostructure

Abstract: We study the ac Josephson effect in a superconductor-ferromagnet heterostructure with a variable magnetic configuration. The system supports triplet proximity correlations whose dynamics is coupled to the magnetic dynamics. This feedback dramatically modifies the behavior of the junction. The currentphase relation becomes double periodic at both very low and high Josephson frequencies ! J . At intermediate frequencies, the periodicity in ! J t may be lost. DOI: 10.1103/PhysRevLett.100.207001 PACS numbers: 74.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…Spincurrents enable a transfer of angular momentum to the magnetic order parameter of a material via the effect of spintransfer torque 43,44 . Since spin-supercurrents also carry angular momentum, the same effect is possible in this context and a few previous works have investigated the possibility of magnetization dynamics in superconducting hybrid structures 45,46,[48][49][50][51]56 . However, it remains unclear how the superconducting phase difference affects the dynamics via the Andreev bound-state spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Spincurrents enable a transfer of angular momentum to the magnetic order parameter of a material via the effect of spintransfer torque 43,44 . Since spin-supercurrents also carry angular momentum, the same effect is possible in this context and a few previous works have investigated the possibility of magnetization dynamics in superconducting hybrid structures 45,46,[48][49][50][51]56 . However, it remains unclear how the superconducting phase difference affects the dynamics via the Andreev bound-state spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Thus such JJs allow one to manipulate the internal magnetic moment by Josephson current 6,9 . The static properties of S/F/S structures are well studied both theoretically and experimentally; however, the magnetic dynamics of these systems has not been studied in detail beyond a few theoretical works 6,[9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…[32][33][34][35] Recently, interest in coupling between the dynamics of magnetic moments and Josephson currents has increased. [36][37][38][39][40][41] In Refs. 42 and 43, it was found that spin-singlet to spintriplet conversion can be generated by a nanomagnet such as an SMM or a ferromagnetic nanoparticle coupled to a Josephson junction 44 provided that the magnetization direction of the nanomagnet precesses.…”
Section: Introductionmentioning
confidence: 99%